Modeling phase equilibria for a water-CO2-hydrocarbon mixture using CPA equation of state in CO2 injection EOR-storage processes: a Colombian case study - Aristizabal Marulanda, Juan David; Cundar Paredes, Cristiam David; Guerrero Benavides, Christian David; Aguirre, Andres; Pasos, Juan Andres; Moncayo Riascos, Ivan Dario; Ruiz, Marco; Benjumea Hernández, Pedro Nel; Agudelo, William Mauricio; Osorio Gallego, Raúl (CT&F - Ciencia, Tecnología y Futuro, 2024)
Currently, it is necessary to reduce CO2 emissions into the atmosphere. The oil industry in Colombia can contribute through CO2 injection processes in depleted fields. To achieve this, it is essential to have knowledge of the physicochemical interactions of CO2 with reservoir fluids. To integrate CO2, water and hydrocarbon phases, advanced models are required that capture the phenomenology of thermodynamic equilibrium. The CPA (Cubic-Plus-Association) equation of state is an equation that adds an associative term to model the interaction of water with the hydrocarbon and CO2 phase. In this work, the CO2 injection process is thermodynamically modeled in a depleted Colombian reservoir case study. There is a compositional fluid with a gradient of PVT properties in a vertical relief of 10,000 ft at a depletion condition of 2,000 psi @ 15,374 ft and an oil-water contact (OWC) at 17,000 ft. CO2 injections between 10 and 80 mol% were carried out, and through the CPA equation of state, the swelling conditions of the crude oil, the solubility of CO2 in the formation water and the pressurization of the system were evaluated. The associative parameters of the equation were taken from literature and estimated through molecular dynamics simulations of water-CO2-Hydrocarbon interactions. This thermodynamic modeling with an advanced equation of state and use of molecular dynamics simulations allowed us to simulate different CO2 injection scenarios in a compositional fluid. The development of these types of studies is key to carrying out successful CO2 injection processes focused on enhanced recovery (EOR) and CO2 storage in the porous medium in a Colombian-depleted compositional reservoir.